PRELIMINARY ANALYSIS BY OPERATING CHAIN OF DEBRIS LITHIC COMPLEX AYACUCHO, PERU - Yataco Capcha, Juan (2009)
The analysis of archaeological lithic material from the Pikimachay cave at the Ayacucho Complex corresponding to the Final Pleistocene, have led to definite typological identifications such as core debris, first and secondary flakes, and fragments of slices which were most likely obtained through soft or hard hammer percussion. This study shows the results of an analysis of metric measurements applied to the collection conducted under the methodology of “Chaîne Opératoire” with the goal of identifying possible measures and the average order sequence for stone carving. However, knowing that we have minimal qualitative evidence on the archaeological lithic material from the Ayacucho Complex, the results of the preliminary analysis have demonstrated the association with three moments of stone carving.